Наголошення інфінітивів у «Енеїді» І. П. Котляревського - Шестопал, О.С. (Мовознавство, 2016)
Статтю присвячено кількісному та якісному аналізу парадигматичної характеристики наголосу інфінітивів поеми «Енеїда». Виявлено факти відхилення від сучасної акцентної норми, висвітлено роль наголосу в диференціації лексичного та граматичного значення в наведених формах. The article deals with quantitative and qualitative analysis of paradigmatic stress characteristic of infinitives from the Ivan Kotlarevsky’s poem «Aeneid». The paper presents examples of infinitive accentuation which does not coincide with the modem accent norm and also focuses on distinguishing lexical and grammar meaning of verbs with the help of stress.